Marketing Strategies, Experiential Marketing, and Public Relations in Increasing the Number of Tourist Visits - Maheswari, Anak Agung Istri Agung; Ariwangsa, Kadek Ryodinero Wahyunanda (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to test and analyze the influence of Marketing Strategy, Experiential Marketing and Public Relations in increasing the number of visits. This research was conducted at the Muntig Siokan Inspiration Park with a research sample of 100 respondents taken using the Slovin formula. All data obtained from the questionnaire distribution is suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The results of the research show that (1) Marketing Strategy has a positive and significant effect in increasing the number of visits to the Muntig Siokan Inspiration Park, so that the more Marketing Strategy increases, the more visits to the Muntig Siokan Inspiration Park (2) Experiential Marketing has a positive and significant effect in increasing the number of visits to the Muntig Siokan Inspiration Park so that the more Experiential Marketing increases, the more visits to the Muntig Siokan Inspiration Park (3) Public Relations has a positive and significant effect in increasing the number of visits to the Muntig Siokan Inspiration Park, so that the more Public Relations increases, the more the number increases. visit to the Muntig Siokan Inspiration Park. (4) Marketing Strategy, Experiential Marketing and Public Relations have a positive and significant effect in increasing the number of visits to the Muntig Siokan Inspiration Park.